Assessment of cross-resistance potential to serial antibiotic treatments in antibiotic-resistant Salmonella Typhimurium. (November 2020) - Dawan, Jirapat; Ahn, Juhee
Abstract: This study was designed to evaluate the cross-resistance of Salmonella Typhimurium ATCC 19585 (ST WT ), ciprofloxacin-resistant S. Typhimurium (ST CIP ), and clinically isolated S. Typhimurium CCARM 8009 (ST CLI ) serially exposed to a half MIC of ceftriaxone (CEF), ciprofloxacin (CIP), polymyxin B (POL), or tetracycline (TET), followed by 1 MIC of CEF, CIP, POL, and TET. The viability changes of ST WT, ST CIP, and ST CLI exposed to different classes of antibiotics were measured to evaluate the development of cross-resistance. The relative fitness was also estimated to evaluate the reproductive success of ST WT, ST CIP, and ST CLI consecutively exposed to a half and 1 MIC of CEF, CIP, POL, or TET. The expression levels of efflux pump-related genes ( acrA, acrB, mdsA, mdsB, mdtB, and tolC ) were evaluated by using a quantitative RT-PCR assay. The MIC of CIP against ST CIP was increased by 128-fold compared to ST WT . ST CLI was highly resistant to POL (MIC = 8 μg/ml) and TET (MIC = 256 μg/ml). ST WT exposed to CIP [1/2] was susceptible to POL [1] than CEF [1], CIP [1], and TET [1], ST CIP exposed to CIP [1/2] was susceptible to CEF [1] and POL [1], and ST CLI exposed to CIP [1/2] was susceptible to POL [1]. ST CIP was cross-resistant to CEF [1/2]-CIP [1], CIP [1/2]-CIP [1], POL [1/2]-CIP [1], and TET [1/2]-CIP (Ochoa et al., 2020) [1]. The efflux pump-related genes ( acrA, acrB, mdsA, mdsB, mdtB, and tolC ) were overexpressed in ST WT, ST CIP, and ST CLI exposed to serial antibiotic treatments, which was related to the development of cross-resistance. The antibiotic susceptibility profiles of ST WT, ST CIP, and ST CLI exposed to serial antibiotic treatments are worth understanding the evolution of antibiotic resistance and developing effective therapeutic regimens against antibiotic-resistant bacteria. Highlights: The sequence of antibiotic treatments contributed to the evolution of antibiotic resistance. The serial antibiotic treatments induced positive and negative cross-resistance. The overexpression of efflux-related genes were directly associated with the antibiotic resistance.